Food safety assessment of Cry8Ka5 mutant protein using Cry1Ac as a control Bt protein. (July 2015) - Farias, Davi Felipe; Viana, Martônio Ponte; Oliveira, Gustavo Ramos; Santos, Vanessa Olinto; Pinto, Clidia Eduarda Moreira; Viana, Daniel Araújo; Vasconcelos, Ilka Maria; Grossi-de-Sa, Maria Fátima; Carvalho, Ana Fontenele Urano
Highlights: Cry proteins possess a well-documented history of safe use and mode of action. Cry8Ka5 mutant protein showed no similarity to allergenic proteins. Cry8Ka5 was degraded in simulated gastric fluid. The LD50 for Cry8Ka5 and Cry1Ac was >5000 mg/kg body weight when administered by gavage in mice. No expected relevant risks are associated with the consumption of Cry8Ka5 protein. Abstract: Cry8Ka5 is a mutant protein from Bacillus thuringiensis ( Bt ) that has been proposed for developing transgenic plants due to promising activity against coleopterans, like Anthonomus grandis (the major pest of Brazilian cotton culture). Thus, an early food safety assessment of Cry8Ka5 protein could provide valuable information to support its use as a harmless biotechnological tool. This study aimed to evaluate the food safety of Cry8Ka5 protein following the two-tiered approach, based on weights of evidence, proposed by ILSI. Cry1Ac protein was used as a control Bt protein. The history of safe use revealed no convincing hazard reports for Bt pesticides and three-domain Cry proteins. The bioinformatics analysis with the primary amino acids sequence of Cry8Ka5 showed no similarity to any known toxic, antinutritional or allergenic proteins. The mode of action of Cry proteins is well understood and their fine specificity is restricted to insects. Cry8Ka5 and Cry1Ac proteins were rapidly degraded in simulated gastric fluid, but were resistant to simulated intestinal fluid and heat treatment. The LD50 for Cry8Ka5 and Cry1Ac was >5000 mg/kg body weight when administered by gavage in mice. Thus, no expected relevant risks are associated with the consumption of Cry8Ka5 protein.